2016
DOI: 10.3847/0004-637x/827/2/151
|View full text |Cite
|
Sign up to set email alerts
|

Flux Cancellation and the Evolution of the Eruptive Filament of 2011 June 7

Abstract: We investigate whether flux cancellation is responsible for the formation of a very massive filament resulting in the spectacular 2011 June 7 eruption. We analyse and quantify the amount of flux cancellation that occurs in NOAA AR 11226 and its two neighbouring ARs (11227 & 11233) using line-of-sight magnetograms from the Heliospheric Magnetic Imager. During a 3.6day period building up to the filament eruption, 1.7 × 10 21 Mx, 21% of AR 11226's maximum magnetic flux, was cancelled along the polarity inversion … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 72 publications
4
48
0
Order By: Relevance
“…The amount of flux canceled is very similar to that found in Yardley et al (2017) despite the difference in methods used to calculate the magnetic flux. This is also consistent with previous studies such as Green et al (2011), Baker et al (2012), and Yardley et al (2016. The AR also rotates clockwise during this period.…”
Section: Summary and Discussionsupporting
confidence: 93%
“…The amount of flux canceled is very similar to that found in Yardley et al (2017) despite the difference in methods used to calculate the magnetic flux. This is also consistent with previous studies such as Green et al (2011), Baker et al (2012), and Yardley et al (2016. The AR also rotates clockwise during this period.…”
Section: Summary and Discussionsupporting
confidence: 93%
“…López Fuentes et al (2000) reported their existence for the first time in a rotating bipolar AR and they were later observed in many other examples (see e.g. Luoni et al 2011;Mandrini et al 2014;Valori et al 2015;Yardley et al 2016;Vemareddy & Démoulin 2017;Dacie et al 2018;López Fuentes et al 2018). They also have been found in numerical simulations of emerging FRs (Archontis & Hood 2010;Cheung et al 2010;MacTaggart 2011;Jouve et al 2013;Rempel & Cheung 2014;Takasao et al 2015).…”
Section: Introductionmentioning
confidence: 90%
“…High decay rates have indeed been measured in complex active regions where not only small flux concentrations but spot-size magnetic fields cancel (e.g. 5 ⇥ 10 20 Mx day 1 cancellation rate found in AR 11226 by Yardley et al, 2016; see also Sterling et al, 2010).…”
Section: Ageing Active Regionsmentioning
confidence: 94%
“…U-loop, see van Driel-Gesztelyi et al 2000) subsurface geometry, or multiple major flux emergence episodes in an active region, which drive large flux concentrations towards the internal inversion line, significantly increasing the cancellation rates there (Yardley et al 2016). The presence of active regions in the vicinity of emerging flux, if they are favorably oriented, can lead to increased cancellation rates along the external boundaries and shortened active-region lifetimes.…”
Section: Ageing Active Regionsmentioning
confidence: 99%
See 1 more Smart Citation